The intensity of using TikTok social media as a mediator of self-esteem and body image in adolescents - Rahmalia, Marsa Nabila; Laili, Latifatul (Jurnal Ilmiah Psikologi Terapan, 2025)
In the rapidly developing digital era, social media such as TikTok have become a part of adolescents' lives and have the potential to influence perceptions of body image. The intensity of TikTok use in adolescents has the potential to mediate the relationship between self-esteem and body image, as this platform is often a space for self-exploration and social comparison. This study aimed to determine the intensity of TikTok's social media use in mediating self-esteem and body image in adolescents. This study used a quantitative approach with a purposive sampling technique. The participants comprised 202 male and female adolescents aged 13 to 18 who completed the Multidimensional Body-Self Relations Questionnaire (MBSRQ-AS), the Rosenberg Self-esteem Scale (RSES), and the intensity of the TikTok social media use scale. Furthermore, a mediation analysis was conducted using Hayes' PROCESS 4 model. The results showed that self-esteem directly impacted adolescents' body image (β = 1.1324; p = 0.0000; and CI = 0.9414 - 1.3233). This finding emphasizes the role of self-esteem in adolescents' body image.